2021
DOI: 10.3390/life11040315
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Abnormalities in Chronic Kidney Disease and Renal Transplantation

Abstract: Chronic kidney disease (CKD) is one of the most important risk factors for cardiovascular disease (CVD). Despite the kidney having no direct implications for lipoproteins metabolism, advanced CKD dyslipidemia is usually present in patients with CKD, and the frequent lipid and lipoprotein alterations occurring in these patients play a role of primary importance in the development of CVD. Although hypertriglyceridemia is the main disorder, a number of lipoprotein abnormalities occur in these patients. Different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 114 publications
(133 reference statements)
1
8
0
Order By: Relevance
“…The current study observed HDL levels to be low in CKD patients on hemodialysis, which is consistent with a study done by Ganta [18]. Our study is also strongly supported by the paper by Barbagallo et al [19]. A possible mechanism involved in low HDL levels is that uremic patients generally exhibit decreased levels of apolipoprotein AI and AII.…”
Section: Discussionsupporting
confidence: 93%
“…The current study observed HDL levels to be low in CKD patients on hemodialysis, which is consistent with a study done by Ganta [18]. Our study is also strongly supported by the paper by Barbagallo et al [19]. A possible mechanism involved in low HDL levels is that uremic patients generally exhibit decreased levels of apolipoprotein AI and AII.…”
Section: Discussionsupporting
confidence: 93%
“…CKD is a known risk factor for cardiovascular disease, since elevated plasma levels of apoA-I containing lipoproteins may lead to the accumulation of atherogenic particles [63,64]. In our study, multiple apolipoproteins were dysregulated with respect to control samples.…”
Section: Discussionmentioning
confidence: 47%
“…Caught between pro-inflammatory signals, disrupted angiogenesis and tissue repair pathways, the kidney suffers from loss of function, which is apparent in lipid metabolism. CKD is a known risk factor for cardiovascular disease, since elevated plasma levels of apoA-I containing lipoproteins may lead to the accumulation of atherogenic particles [ 63 , 64 ]. In our study, multiple apolipoproteins were dysregulated with respect to control samples.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, CKD is characterized by an accumulation of VLDL (very-low-density lipoprotein) particles, a reduction of LDL particle size, and changes in the cholesterol and triglyceride content in LDL and HDL (high-density lipoproteins, which gain triglycerides and lose cholesterol). Notably, HDL in CKD patients turned out to lose its atheroprotective properties and even harm the vasculature [ 25 ].…”
Section: Cardiovascular Risk In Ckdmentioning
confidence: 99%